Ileus Biliaire : A Propos D’un Cas Clinique - A., Saidou; A., Herrero; K., Ide; L., James Didier; H., Younssa; R., Sani (European Scientific Journal, ESJ, 2017)
Introduction: Gallstone ileus is a rare mechanical occlusion. It is caused by the enclosure of biliary macro lithiasis in a portion of the digestive tract resulting from a digestive bile fistula. We report a clinical case to discuss therapeutic modalities through a review of the literature. Medical observation: We report the case of a 77-year-old patient who was hospitalized in the Nephrology department of the university hospital in Montpellier for functional kidney failure and dehydration from vomiting and diarrhea. The none-injected abdominal-pelvic CT scan showed a gallstone ileus with 5 enclaved duodenum, jejunum and ileum lithiasis resulting into a small bowel obstruction. There are no signs of acute cholecystitis. The management was simple by enterolithotomy surgery alone after fixing of hydro electrolyte imbalance. The after surgery sequence was simple. Conclusion: Gallstone ileus is a rare surgical condition. The high mortality rate in the management of this condition makes enterolithotomy the least invasive and recommended method.